1994
DOI: 10.1007/bf00310401
|View full text |Cite
|
Sign up to set email alerts
|

Relations between calcidiol serum levels and bone mineral density in postmenopausal women with low bone density

Abstract: The relationship between vitamin D and bone density was studied in 150 selected, mature (45-74), postmenopausal women with a lumbar spine Z score below 0. Vitamin D status was evaluated using calcidiol serum levels. Serum calcitriol and parathyroid hormone (PTH) values were also evaluated in some subjects. Bone mass was evaluated by ascertaining bone density and Z and T scores in the lumbar spine and femur region. The reference group consisted of 25 premenopausal women. The postmenopausal group was divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 21 publications
2
16
2
Order By: Relevance
“…This is in accordance with a recent metaanalysis, where no effect of smoking could be detected until menopause, while de®cits of 2% for every 10 year increase in age were seen after the menopause (Law & In¯uence of smoking on vitamin D status and calcium metabolism C Brot et al Hackshaw, 1997). An association between circulating concentrations of 25OHD and bone density has been demonstrated in a number of studies (Khaw et al, 1992;Martinez et al, 1994). The relationships between bone density and vitamin D metabolites and PTH in the present study were modest or absent.…”
Section: Discussioncontrasting
confidence: 55%
“…This is in accordance with a recent metaanalysis, where no effect of smoking could be detected until menopause, while de®cits of 2% for every 10 year increase in age were seen after the menopause (Law & In¯uence of smoking on vitamin D status and calcium metabolism C Brot et al Hackshaw, 1997). An association between circulating concentrations of 25OHD and bone density has been demonstrated in a number of studies (Khaw et al, 1992;Martinez et al, 1994). The relationships between bone density and vitamin D metabolites and PTH in the present study were modest or absent.…”
Section: Discussioncontrasting
confidence: 55%
“…Although Chapuy et al [26] did not find any correlation between 25-hydroxyvitamin D or PTH and hip BMD, Ooms et al [27] found a correlation coefficient between BMD of the femoral neck and PTH of -0.270 (p<0.001) in 330 women aged +_ 80.3 years. Martinez et al [28] found a correlation between 25-hydroxyvitamin D and BMD of the femoral neck with a correlation coefficient of 0.290 (,9 < 0.005) in 62 women aged more than 68 years. Szluc et al [29] published data on the relationship between hip BMD and anthropometric parameters and biochemical markers in 98 elderly institutionalized women aged ± 81.4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D plays a central role in bone mineralisation by regulating calcium and phosphate metabolism (Suda et al, 2003), such that vitamin D deficiency leads to hyperparathyroidism, increased bone turnover, rickets, osteoporosis and mild osteomalacia, and an increased risk of hip and other fractures (Dawson-Hughes et al, 1991;Hutchison and Bell, 1992;Martinez et al, 1994;Aguado et al, 2000;Cheng et al, 2003;Isaia et al, 2003). More recently, observational studies have also reported that vitamin D intake is inversely associated with the incidence of a number of conditions, including cancer and autoimmune disorders such as rheumatoid arthritis, multiple sclerosis and type I diabetes mellitus (Bostick et al, 1993;Hypponen et al, 2001;Merlino et al, 2004;Munger et al, 2004).…”
Section: Introductionmentioning
confidence: 99%